Diamond in the Rough: Toward Improved Materials for the Bone−Implant Interface. Issue 14 (25th June 2021) - Fong, Jessica S. L.; Booth, Marsilea A.; Rifai, Aaqil; Fox, Kate; Gelmi, Amy
Abstract: The ability of an orthopedic implant to integrate successfully with the surrounding bone tissue is imperative for optimal patient outcomes. Here, the recent advances and future prospects for diamond‐based coatings of conventional osteo‐implant materials (primarily titanium) are explored. The ability of these diamond coatings to enhance integration into existing bone, improved implant mechanical properties, facilitate surface chemical functionalization, and provide anti‐microbial properties are discussed in context of orthopedic implants. These diamond‐based materials may have the additional benefit of providing an osteo‐inductive effect, enabling better integration into existing bone via stem cell recruitment and bone regeneration. Current and timely research is highlighted to support the discussion and suggestions in further improving implant integration via an osseoinductive effect from the diamond composite materials. Abstract : Diamond‐based coatings of conventional osteo‐implant materials present an opportunity for enhancing implant integration into existing bone, improved implant mechanical properties, surface chemical functionalization, and anti‐microbial properties. The inclusion of diamond may also have the additional benefit of an osteo‐inductive effect, enabling better integration into existing bone via stem cell recruitment and bone regeneration.